An Islamic Economic Law Analysis of Online Almsgiving Practices through the Digital Platform in the Dompet Dhuafa Application - Dwiyulianthi, Anisya; Sofyanti, Rahma Siti; J, Jaenudin; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the implementation of online almsgiving (sedekah) on the Dompet Dhuafa platform from an Islamic sharia perspective using a qualitative approach with a descriptive method supported by in-depth interviews. The findings show that online almsgiving complies with sharia principles based on the Qur’an, Hadith, and fiqh rules that permit the use of technology as a means of worship. The system operates through an integrated digital platform with transparent mechanisms, oversight by a Sharia Supervisory Board, and independent audits with an unqualified (WTP) opinion. Online almsgiving significantly increases the number of donors due to accessible features, wide outreach, and efficient processes. Challenges include varying levels of digital literacy, technical limitations, and public concerns regarding sharia validity. These are addressed through continuous education, enhanced security, maximum transparency, and hybrid service models. The study concludes that digital transformation in almsgiving demonstrates Islam’s adaptability while upholding sharia values and optimizing the potential of Islamic philanthropy for greater social impact in the digital era.